2013
DOI: 10.4238/2013.october.7.1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the pseudorabies virus UL2 gene

Abstract: ABSTRACT.A 948-bp sequence of the UL2 gene was amplified from the pseudorabies virus (PRV) Becker strain genome using polymerase chain reaction, and the gene identity was confirmed through further cloning and sequencing. Bioinformatic analysis indicated that the PRV UL2 gene encodes a putative polypeptide with 315-amino acid residues. Its encoding protein, designated UL2, has a conserved uracil-DNA glycosylase (UDG)_F1 domain, which is closely related to the herpesvirus UDG family and is highly conserved among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Herpesviral UDG is reported to be a multi-functional protein, which is highly conserved and important for the production of viral DNA among HSV-1 UL2, HSV-2 UL2, pseudorabies virus (PRV) UL2, HCMV UL114, varicella-zoster virus ORF59 and human herpesvirus 6 U81. Specifically, UDG is involved in the base cutting repair pathway, which correctly detaches the erroneously inserted uracil from synthetic viral DNA [5,8,33]. Studies have shown that the NLSs of some viral proteins are required for the efficient virus replication.…”
Section: Agingmentioning
confidence: 99%
“…Herpesviral UDG is reported to be a multi-functional protein, which is highly conserved and important for the production of viral DNA among HSV-1 UL2, HSV-2 UL2, pseudorabies virus (PRV) UL2, HCMV UL114, varicella-zoster virus ORF59 and human herpesvirus 6 U81. Specifically, UDG is involved in the base cutting repair pathway, which correctly detaches the erroneously inserted uracil from synthetic viral DNA [5,8,33]. Studies have shown that the NLSs of some viral proteins are required for the efficient virus replication.…”
Section: Agingmentioning
confidence: 99%
“…After the PCR amplified product was validated as the intended product, it was purified using a PCR gel purification kit (Qiagen) according to the manufacturer’s instructions. The product was then digested with EcoR I and BamH I and inserted into the correspondingly digested green fluorescent protein variant mammalian expression vector pEYFP-N1 (Clontech) encoding EYFP at 16 °C overnight using T4 DNA ligase, to create the recombinant plasmid named pP-ICP22-EYFP, as described previously [ 3 , 26 , 50 53 ]. After mini-scale isolation of plasmid DNA using Qiagen plasmid Mini kits (Qiagen), the presence of the appropriate insert in the obtained plasmid was confirmed by PCR, restriction analysis and sequencing.…”
Section: Methodsmentioning
confidence: 99%